2013
DOI: 10.1007/s10903-013-9888-3
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of Infectious Diseases in Immigrants in a Western European Country: A Population-Based Study

Abstract: The aim of this population-based study was to assess the incidence rates of infectious diseases in native- (Italian) and foreign-born (immigrants) populations in a North Italy area, in 2006-2010. Crude, age-specific incidence rates (IRs) and age-standardised rate ratios (SRRs) between foreign- and native-born subjects and their 95% confidence intervals (95% CI) were estimated. A total of 32,554 cases of infectious diseases were found (9.9% in foreign-born subjects). The highest SRRs between foreign- and native… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Several trends and related factors have been found to be important for scabies outbreaks. Thus, a strong connection among scabies, migration and travel has been reported ( 11 , 12 , 15 , 23 ). Since scabies moves with people, mass migration due to political and socioeconomic factors can promote its spread, as seen recently with the influx of asylum seekers arriving in Western Europe from high-prevalence countries ( 11 , 12 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several trends and related factors have been found to be important for scabies outbreaks. Thus, a strong connection among scabies, migration and travel has been reported ( 11 , 12 , 15 , 23 ). Since scabies moves with people, mass migration due to political and socioeconomic factors can promote its spread, as seen recently with the influx of asylum seekers arriving in Western Europe from high-prevalence countries ( 11 , 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since scabies is transmitted by close person-to-person contact, it is logical that outbreaks have been reported in reception centres for asylum seekers across Europe ( 11 ). Previous studies claim that immigrants are at a higher risk of acquiring common communicable diseases compared to the native Western European population ( 23 ). Although most refugees in Croatia are only in transit, refugee and migration flows can still have an impact on the occurrence of scabies in the country.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immigrants in general are also more susceptible to infectious disease compared to native populations [ 36 , 37 ]. Limina et al [ 36 ] found that the reasons for this increased likelihood of contracting infectious disease are the socioeconomic situations in the country in which they are living.…”
Section: Determinants Of Health Risk Perceptionmentioning
confidence: 99%
“…Immigrants in general are also more susceptible to infectious disease compared to native populations [ 36 , 37 ]. Limina et al [ 36 ] found that the reasons for this increased likelihood of contracting infectious disease are the socioeconomic situations in the country in which they are living. Some of these situations are exacerbated by immigration status in the host country, social exclusion, discrimination, language difficulties, gender, and access to medical services, among other things [ 2 , 36 ].…”
Section: Determinants Of Health Risk Perceptionmentioning
confidence: 99%